Application of a New Established System for Toxic Doses in Children With 4-Hydroxycoumarin Rodenticide Intoxication - Li Ye; Li Ye; Zheng Wang; Hui Zhang; Hui Guo; Yannan Guo; Lina Chen (Frontiers Media S.A., 2018)
The toxic dose of rodenticides in children is extremely difficult to be determined because of the uncertain exposure history. We established and validated a method to identify the toxic dose in children of 4-hydroxycoumarin (TDCH). Items were selected by Delphi method and weighted by analytic hierarchy process. Toxic doses were classified into three categories: high dose (>24 points), medium (15-24) and low (<15). Sixty-five children with 4-hydroxycoumarin rodenticide intoxication were included in the study. There were 29(44.6%), 8(12.3%), 28(43.1%) cases in high, medium, and low dose respectively. Patients in high-dose were more likely to have intentionally attempted suicide (5/29, 17.2%) or had no definite history of ingestion (17/29, 58.6%), arrived at the hospital later than 24 h (26/29, 90%), been misdiagnosed initially (25/29, 86.2%), not treated by gastric lavage (27/29, 93.1%), and developed severe hemorrhage. While most patients in low-dose were younger than 6 years (26/28, 92.9%), all have experienced accidental exposure, arrived at the hospital, and received gastric lavage within 24 h, obtained a definite diagnosis, and be asymptomatic. Of 38 patients arrived at hospital within 48 h, patients a score48h ≥ 15 had higher incidence of coagulopathy (6/8, 75.0%) than patients with a score48h < 15 (3/30, 10.0%). Of all patients, 37 in the high and medium dose with a score ≥ 15 has higher incidence (35/37, 94.6%) of prolonged administration with vitamin K1 (≥1 month) than other 28 patients with a score < 15 (0/28, 0%). The TDCH system could not only be used in evaluating toxic doses and predicting coagulopathy in the early stage, but also helps to guide appropriate treatment. Patients with a score48h ≥ 15 were in the high bleeding risk category. And patients with a scores ≥ 15 required treatment with vitamin K1 for more than a month.